PENGARUH SUPERVISI KEPALA SEKOLAH DAN INOVASI KURIKULUM TERINTEGRASI OLEH TENAGA KEPENDIDIKAN TERHADAP PROFESIONALISME GURU DAN PRESTASI BELAJAR SISWA DI MA AL UM PINANG RAYA KABUPATEN BENGKULU UTARA - Giyarsi Giyarsi (IAIN Bengkulu, 2018)
The purpose of this study is to examine whether there is influence of principal supervision and innovation of in- tegrated curriculum development by educational staff on teacher professionalism and student achievement, either direct or indirect influence. This research is a non experimental quantitative research using data analysis method with path analysis statistical test (path analysis). The results showed two conclusions. First there is the direct and indirect influence of the principal supervisory variables and the innovative variables of integrated curriculum development by the educational staff on teacher professionalism variables. The magnitude of this influence is the direct influence of principal supervision on the professionalism of teachers by 2.37%, the direct influence of integrated curriculum development innovation on professionalism of teachers by53.29%, indirect influence of principal supervision and innovation of integrated curriculum development on teacher profes- sionalism of 7 , 37%, and total influence on teacher professionalism equal to 68,03%. Second, there are direct and indirect influence of principal supervision variable, innovation variable of integrated curriculum development by educational staff, and teacher professionalism variable to learning achievement variable. The amount of influence is the direct influence of principal supervision on student achievement of 1.32%, with indirect effect of 13.26%. The direct effect of integrated curriculum devel- opment innovation on student achievement is 1.41%, with indirect effect of 62.85%. The direct influence of teacher profes- sionalism on student achievement is 74.13%. And the total influence on student achievement of the three variables is 77.52%. That is, partially, principal supervision and innovative curriculum development development by uneducated educational staff on student achievement in MA Al Um Pinang Raya, but simultaneously together with the professionalism of teachers give a big positive impact.